The giftie gien - Jameson, Malcolm, 1891-1945; Kramer, Frank, 1905-1993 (Salt Lake City, UT : Project Gutenberg, 2022)
"The giftie gien" by Malcolm Jameson is a short story published in the early 1940s. This speculative fiction piece explores the themes of self-awareness and the perception of one's character and actions through the lens of afterlife judgment. The narrative begins with the mundane interactions of a sales manager and transitions into a surreal exploration of the protagonist's essence after his sudden death. In the story, we follow Jerome Chester Chisholm, a self-satisfied sales manager who is brutally murdered after dismissing the struggles of his underperforming employees. Following his death, he discovers an eerie afterlife where he encounters a demon and is forced to face the judgments of various individuals whose lives he impacted$1 (Bboth positively and negatively. As the manifestations of all the people he's interacted with blend into a grotesque version of himself, Chisholm is confronted with the harsh reality of his self-centered existence, ultimately leading to a profound moment of self-reflection and accountability. Through this journey, the story critiques the nature of self-perception and the importance of understanding how one is perceived by others. (This is an automatically generated summary.)s
Release date is 2022-12-30
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Short stories; Fantasy fiction; Businessmen -- Fiction; Future life -- Fiction